INVESTIGATION OF MORPHOLOGICAL AND ANTIMICROBIAL PROPERTIES OF INTESTINAL TRACT MICROORGANISMS - Shishin M.V.; Prosekov A.Y. (Техника и технология пищевых производств)
The intestinal microbiota plays an important role in the normal functioning of the intestine and maintaining the health of the organism. Microorganisms from intestinal tracts of healthy people and cancer patients were isolated and identified. The culture and the morphological properties of microorganisms were studied on solid medium. During the study the diameter of the colonies in millimeters, color, shape, texture, structure, surface, edge contour character were determined. The nature of the bacterial growth in the liquid media (bottom, parietal or surface, with uniform medium turbidity) was analyzed. The main method of studying the morphology of the bacteria was microscopy of fixed stained preparations. It is shown that the intestinal tract of healthy people and cancer patients contains bacteria of the following genera: . Also the following fungi were isolated from human intestinal tract: Candida and Cryptococcus. The results indicate that the following microorganisms show the maximum antimicrobial activity: (the diameter of test culture growth inhibition zones is from 28.9 mm to 37.0 mm), Bifidobacterium breve (the diameter of inhibition zones - from 26.8mm to 35.6 mm), (the diameter of inhibition zones - from 24.9 mm to 38.2 mm), (the diameter of inhibition zones - from 25.2 mm to 36.7 mm), (the diameter of inhibition zones - from 27.6 mm up to 38.4 mm).